A Critique of the Controlled Defining Vocabulary in Longman Dictionary of Contemporary English - Hai Xu (Woordeboek van die Afrikaanse Taal-WAT, 2012)
This article critically analyses the Longman Defining Vocabulary (LDV) in relation to its size, range and frequency, senses, parts of speech, affixes, and multiword expressions. The recent versions of the LDV contain a relatively fixed number of items. Over 85% of those items were found to be highly frequent, and for the defining purpose, genus terms, grammatical terms, etc. have also been included. The number of affixes in the LDV has been greatly reduced, and some common derivatives have been listed separately. On the other hand, the actual size of the LDV is much larger than was reported, for LDOCE did not distinguish between the LDV items with different senses or forms. It was found that the claim of using the 'most common meanings' of the LDV items is not always held true. The parts of speech of the LDV items have not been systematically indicated. Many multiword expressions, which have been used in the definitions in LDOCE, are not part of the LDV. This study sheds some light on the improvement in the practice of using a controlled defining vocabulary in an English learner's dictionary.